The Effects of Lecture Diversity on Germane Load - Costley, Jamie; Lange, Christopher Henry (International Review of Research in Open and Distributed Learning, 2017)
An important aspect of MOOCs is the way students interact with video lectures. Instruction provided through video lectures should focus on ways to increase germane cognitive load, which directly contributes to learning. One approach that may lead to an increase of germane load may be to use video lectures with diverse forms of media, including both auditory and visual aspects of multimedia. This study surveyed a group of students (n = 1602) who participated in MOOC-like courses in South Korea to investigate the relationship between delivery diversity and germane cognitive load. Additionally, the relationships between individual indicators of both audio and visual aspects of multimedia and germane load were examined. Results show a positive relationship between diverse media delivery (auditory, visual, and total media) and germane cognitive load. The implication of these results are important for instructors who wish to promote a better understanding of e-learning materials through the delivery of content by using diverse forms of media.